Visitors of World Heritage - Bahram Ghadiri (صفه)
The present article is the translation of the tenth chapter of the book "Management Guidelines for World Cultural Heritage Sites" by Bernard M. Feilden and Jukka Jokilehto published by the International Center for the Study of the Preservation and the Restoration of Cultural Property in 1993